The Physical Properties, Fiber Morphology and Chemical Compositions of Sweet Bamboo (Dendrocalamus asper Backer) - Suphat Kamthai; Pratuang Puthson (Agriculture and Natural Resources, 2005)
The physical properties, fiber morphology and chemical compositions of sweet bamboo (Dendrocalamus asper Backer) were investigated for utilization in pulp and papermaking. The results indicated that the variation of sweet bamboo properties along the culm depended on position (base, middle and top) and part (node and internode). The basic density and moisture content of sweet bamboo were 725 kg/m3 and 60.24%, respectively. Data collected from sweet bamboo fiber morphology illustrated its fiber dimensions as follows: fiber length 3.11 mm, fiber width 18.03 μm, cell wall thickness 6.98 μm and cell lumen 4.35 μm. The chemical compositions were holocellulose 76.33%, alpha-cellulose 68.11%, lignin 28.70% and ash 1.46%. The solubility in different solvents were alcohol-benzene 5.91%, hot water 8.04%, cold water 7.03% and 1% NaOH 24.91%. According to the results, sweet bamboo has potential as a raw material for long fiber production in Thailand.